Project quality management : why, what and how - Rose, Kenneth, 1947- (J. Ross Publishing, 2022)
"Project Quality Management: Why, What and How, recipient of the PMI David I. Cleland Project Management Literature Award in its first edition, offered project managers a specific, succinct, step-by-step project quality management process found nowhere else. This third edition has been updated and enhanced to also meet the needs of trainers, college instructors, and their students!"--